An evaluative study of the existing guidance program of Saint Paul College grade school - Marasigan, Corazon M. (Animo Repository, 1975)
This study evaluates the existing guidance program of Saint Paul College Grade School. The data for this study were obtained from information handed by counselors, teachers and students of Saint Paul College Grade School. Four hundred students from Grades IV-VII were randomly selected from the 1028 population which is composed of the intermediate level. Each intermediate level was represented by 100 students. They were already capable of making judgment. And 50 out of 60 faculty members responded and 3 counselors were included. The study revealed that teachers, students, and counselors perceived the same problems and these are related to social relationships with friends, parents, siblings and teachers. Academic problems as difficulty in getting good grades is also one of the problems common to them. Students and teachers have favorable attitude toward the school guidance program. However, it was found out that faculty members lack necessary background or formal training in guidance and counseling. Teachers and counselors believed that the present guidance objectives are based on the needs of, and are relevant to students. The pressing problems presently met by the counselors are those regarding guidance programs and objectives and services, guidance staff roles, budget, guidance involvement and the teachers' guidance orientation. And some of the recommendations drawn were as follows : 1) the proposed in-service education for faculty members should be conducted for a better guidance awareness and orientation of teachers. 2) the proposed revisions on guidance services should be implemented. Teachers involvement and participation should be solicited so that guidance will be better conceived as a cooperative enterprise. 3) a full-hearted support and cooperation of the administration is very necessary, and 4) a possibility of an in-service training program for parents should be looked into the near future.